(untitled) (Sustainable Development Insights, 2026)
This study aims to map the intellectual structure, thematic development, and research trends in climate action using a bibliometric approach. Data were collected from a reputable scientific database and analyzed using VOSviewer to examine co-occurrence patterns of keywords, network relationships, and thematic evolution. The findings reveal that climate change serves as the central node connecting multiple research domains, indicating a highly integrated and multidisciplinary field. Three dominant thematic clusters emerge, namely mitigation-oriented research focusing on carbon emissions and energy transition, ecological studies emphasizing biodiversity and environmental protection, and adaptation and governance research highlighting resilience, risk assessment, and decision-making processes. The overlay visualization shows a temporal shift from impact-oriented studies toward more solution-driven themes such as sustainability, climate policy, and energy efficiency. Meanwhile, density analysis indicates that research remains concentrated on climate change and sustainable development, while adaptation and governance themes are still developing. This study contributes by providing a comprehensive overview of the structure and evolution of climate action research, as well as identifying potential directions for future studies, particularly in integrating mitigation, ecological, and governance perspectives into a more holistic framework.